Survey of the Implementation of Professional Learning Community (PLC) Program in Primary Schools - Sunaengsih, Cucun; Komariah, Aan; Isrokatun, Isrokatun; Anggarani, Mayang; Silfiani, Sindy (Universitas Pendidikan Indonesia, 2019)
This research aims at illustrating the implementation of Professional Learning Community (PLC) programs, which later will be used to be the basic data for the preparation of PLC program design that is applicable and easily implemented by the teachers. The low contribution and discontinuity of teachers in the PLC programs in primary schools have impacted on the lack of optimization of the PLC programs as a support for sustained improvement of teacher professionalism. This research employed a descriptive research design with a survey approach involving 52 primary school teachers in Sumerdang Regency. The research results revealed that even though the teachers’ understanding of the PLC program objectives was very high, the teachers’ understanding of the PLC program mechanism was still low. Thus, this resulted in the low level of the implementation of the PLC program in primary schools, both in programs and regulations. Therefore, further research is expected to produce the operational, structured, and applicable PLC programs in order to increase the teachers’ participation in implementing the PLC programs for improving teacher professionalism, and having a real impact on the improvement of the quality of learning in primary schools.